Properties of particleboards made from rubberwood (hevea brasiliensis) and kenaf (hibiscus cannabinus l.) core. / Syed Muhammad Azlan Sayed Idrus, Wan Mohd Nazri Wan Abdul Rahman and Jamaludin Kasim - Sayed Idrus, Syed Muhammad Azlan; Wan Abdul Rahman, Wan Mohd Nazri; Kasim, Jamaludin (2012)
This study investigates the potential of kenaf core (KC) as a substitute material to rubberwood (RW) for producing particleboard. RW particle were mixed with KC particle with ratio 10, 20, 30, 40, and 50% produced into 700 kgm3 target density particleboard with resin content of 10% using urea formaldehydes resin. By handling this investigation, mixing ratio between RW and KC particle are significantly affecting the physical and mechanical properties of board, The additional of KC particle showed the decrease of both physical and mechanical properties of board. The modulus of rupture (MOR) of 50% mixing of KC particle were decrease 28%, modulus of elasticity (MOE) decrease 24%, internal bonding (IB) decrease 47%, TS increase 50%, compare with board of 100% RW particle. All mixing ratios are exceeding the minimum requirement for the mechanical properties based on European Standard (EN 3 10) except for physical properties where the minimum requirement for thickness swelling (TS) value could not achieved 12%.